(untitled) - Lê, Ngọc Vân Thủy (Cần Thơ, 2011)
This study attempts in teaching reading as well as to see whether students’ reading comprehension ability can develop through teachers’ providing background knowledge in reading lessons in the course-book
Keywords: Kiến thức nền tiếng Anh,Background knowledge,Reading comprehension ability,Khả năng đọc hiểu tiếng Anh